PENGEMBANGAN MODEL PEMBELAJARAN KOOPERATIF MENGGUNAKAN PENDEKATAN REALISTIK PADA MATA KULIAH STATISTIKA MATEMATIKA I - Sutrisni Andayani; Jazim Jazim (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
The purpose of this research is developing the cooperative model by using the realistic approach in Mathematic Statistics I. As the form of development and research, collecting data done through observation method, questionnaire, interviewing, and a test. The step of this research are introduction study, plan, develop and evaluation. Based on the introduction study, was developed of cooperative instructional and realistic approach instructional. Syntax in cooperative instructional model done by realistic approach is running well and there are increasing of activity, response and student’s learning achievement, and difference of probability explanation using realistic approach. Syntax instructional of the model are 1) material explanation 2) group discussion by using context, model, alternative in problem-solving and finally concluding of all, 3) the group member is given the quiz individually, and 4) the score and reward are given to the group. Keywords: cooperative instructional model, mathematic statistics I, realistic approach